Analysis of Coconut Supply Chain as Industry Potential in Sula Islands Regency, North Maluku Province - Sutoni, Akhmad (Jurnal Media Teknik dan Sistem Industri, 2020)
Abstract— The supply chain management of the coconut industry in the Sula Islands district is still felt to be ineffective and inefficient. The advantage of effective supply chain management is to get maximum speed when goods and services move through the supply chain channel, lower costs, and increase added value for customers and product competitiveness in the market. The purpose of this study is to identify and analyze the management of the coconut industry supply chain. The method used is descriptive qualitative analysis. Those who play a role in the coconut supply chain in the Sula Islands district are farmers, collectors I, collectors II, owners of home industries, transport vehicle owners and marine vessels as modes of transportation. With this supply chain channel, there are only a few benefits for farmers and business operators. The added value of coconut and copra is very small, meaning that the economic value obtained is very small. To provide greater economic value for residents of the Sula Islands district, especially for coconut farmers and coconut entrepreneurs, so coconut fruit must be processed not only until copra, but made in industrial scale coconut oil.Keywords— Supply Chain; Coconut; Industry; Coconut oil; Sula Islands Regency. Abstrak— Manajemen rantai pasok industri kelapa di kabupaten Kepulauan Sula masih dirasakan belum efektif dan efisien. Keuntungan manajemen rantai pasok yang efektif adalah   untuk   mendapatkan   kecepatan   maksimal pada saat barang dan jasa bergerak melalui jalur rantai pasok, menurunkan biaya, serta meningkatkan nilai tambah bagi pelanggan dan daya saing produk di pasar. Tujuan dari penelitian ini adalah mengidentifikasi dan menganalisis   pengelolaan   rantai   pasokan industri kelapa. Metode yang digunakan adalah Analisis deskriptif kualitatif.  Yang berperan dalam rantai pasokan kelapa di kabupaten Kepulauan Sula adalah petani, pengepul I, pengepul II, pemilik industri rumahan, pemilik kendaraan angkut dan kapal laut sebagai moda transportasi. Dengan jalur Rantai Pasokan seperti ini hanya sedikit keuntungan yang didapat oleh petani maupun pelaku usaha. Nilai Tambah dari Kelapa dan Kopra sangat kecil, berarti Nilai ekonomi yang didapatpun sangat kecil. Untuk memberikan nilai ekonomi lebih besar bagi penduduk kabupaten Kepulauan Sula, terutama bagi petani Kelapa dan pelaku usaha Kelapa, makanya buah Kelapa harus diolah tidak hanya sampai Kopra, tetapi dibuat minyak Kelapa berskala industri.Kata kunci— Rantai Pasok; Kelapa; Industri; Minyak Kelapa; Kabupaten Kepulauan Sula.